Specific Changes in the Composition of Peripheral Blood in Women During the Postpartum Period - Abdullayeva M.A. (Genius Journals, 2022)
During the period of pregnancy, the woman's body undergoes a lot of adaptive processes, these changes prepare the fetus for normal development, development, maturation of the ovarian-uterine system and uncomplicated childbirth. At the same time, some hidden diseases appear during pregnancy, which may not be clinically apparent during pregnancy, but may manifest after childbirth [4,8,10,11,12,13]. Therefore, the importance of changes in peripheral blood in the last stages of pregnancy, in the postpartum period, remains an urgent problem. It is known from modern medicine that the composition of peripheral blood during pregnancy undergoes significant changes during the development of pregnancy and the postpartum period
Keywords: Ovarian-Uterine System; Peripheral Blood; Pregnancy; Postpartum Period